2022
DOI: 10.1186/s12954-022-00634-4
|View full text |Cite
|
Sign up to set email alerts
|

“They say it’s fentanyl, but they honestly look like Perc 30s”: Initiation and use of counterfeit fentanyl pills

Abstract: Background Worsening of the overdose crisis in the USA has been linked to the continuing proliferation of non-pharmaceutical fentanyl (NPF). The recent wave of NPF spread in the USA has been fueled by an increased presence of counterfeit pills that contain NPF. This qualitative study aims to characterize the motivation and practices of counterfeit NPF pill initiation and use among individuals using illicit opioids in Arizona. Methods Between Octob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 40 publications
(41 reference statements)
0
21
0
Order By: Relevance
“…Over the past decade, there was emerging unpredictability and accessibility of NPF and its analogs. 6 There is still much to learn about the pharmaceutical properties and safety profiles of these analogs, which further exacerbates the emerging issue. Fentanyl testing strips have grown in popularity to help individuals with safer drug use practices, but they are considered illegal to use in outpatient clinics per the DEA; advanced and legal technology to detect NPF and analogs more easily and accurately is required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past decade, there was emerging unpredictability and accessibility of NPF and its analogs. 6 There is still much to learn about the pharmaceutical properties and safety profiles of these analogs, which further exacerbates the emerging issue. Fentanyl testing strips have grown in popularity to help individuals with safer drug use practices, but they are considered illegal to use in outpatient clinics per the DEA; advanced and legal technology to detect NPF and analogs more easily and accurately is required.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 1 , a recent study in Arizona found a dramatic increase in the availability of NPF attempting to mimic 30 mg oxycodone, popularly known as “dirty thirties” or “M-30 tabs”. 6 The similarities between these tablets and commonly used pharmaceutical drugs likely reduced the risk perception for people who use drugs, especially compared to heroin. Additionally, NPF is significantly easier to manufacture and distribute, leading to reduced prices in comparison to heroin and pharmaceutical opioids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Counterfeit pharmaceutical drugs-especially those containing illicitly manufactured fentanyls (IMF)are playing an increasing important role in the United States (US) overdose crisis [5][6][7] . IMF and other synthetic opioids have transformed the risk environment for people who use drugs (PWUD) given their much higher potency and shorter half-life compared to other opioids.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been driving a large relative increase in the overdose death rate of adolescents 7 , who are more likely to experiment with drugs they perceive as prescription pharmaceuticals relative to powders sold as heroin, or other drugs that are more stigmatized 14 . For the general population, there is a profound added risk of counterfeit prescription medications relative to other fentanyl-based illicit drug formulations, as pills purporting to be pharmaceuticals may be perceived as a lower-risk category of recreational drugs 6 , despite currently representing one of the most potentially lethal options for illicit drug use, especially because they may be more likely to be used by individuals with no tolerance to opioids. Although counterfeit prescriptions are described in the US illicit drug market-and it is well-known that a large portion of the IMF and methamphetamine that are pressed into counterfeit prescription drugs sold in the US originate in Mexico 15,16 -the prevalence of their consumption among PWUD in Mexico is not well-described in academic literature.…”
Section: Introductionmentioning
confidence: 99%